2014
DOI: 10.2478/bvip-2014-0049
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical parameters of rats’ skin after the administration of methimazole

Abstract: The paper describes the influence of oral administration of methimazole on biophysical skin parameters. Wistar rats of different sex (220-260 g) were used in the experiment. Biophysical skin parameters, such as transepidermal water loss (TEWL), corneometry, and pH were examined at seven-day intervals. Significant changes in the parameters were observed on the 7 th d of methimazole administration. The changes were observed in both sex but males appeared to be less sensitive in that respect. Changes in the param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…After this period, the rats were fed a commercial diet for laboratory animals (Agropol, Poland). Rats from the control group had access to tap water ad libitum , and the rats from experimental groups were given a 0.05% methimazole (Sigma-Aldrich, USA) water solution, administered ad libitum and known to be a dose that was very effective at inducing hypothyroidism (10). A fresh solution was prepared daily.…”
Section: Methodsmentioning
confidence: 99%
“…After this period, the rats were fed a commercial diet for laboratory animals (Agropol, Poland). Rats from the control group had access to tap water ad libitum , and the rats from experimental groups were given a 0.05% methimazole (Sigma-Aldrich, USA) water solution, administered ad libitum and known to be a dose that was very effective at inducing hypothyroidism (10). A fresh solution was prepared daily.…”
Section: Methodsmentioning
confidence: 99%
“…The methods in question are also becoming increasingly popular in veterinary medicine, especially in scientific research. Biophysical skin parameters (TEWL, SH, skin pH) have been assessed in dogs, cats, horses and laboratory animals (Matousek and Campbell 2002, Watosn et al 2002, Popiel and Nicpoń 2004, Fluhr et al 2006, Yoshihara et al 2007, Shimada et al 2008, Szczepanik et al 2011, 2012, Gołyński et al 2014. The most commonly applied parameter has been TEWL, and most of the studies have concentrated on dogs.…”
Section: Introductionmentioning
confidence: 99%
“…The pH of the rat skin is normally ~5-6, 37 and we observed that the skin pH did not change upon massage with the samples. Therefore, when the samples were massaged into the rat skin, they were actually exposed to the pH 5-6 environment, and the sustained release of retinal from PRN similar to that observed in the in vitro release experiment (at pH 5) probably took place.…”
Section: Tolerance Profiles and Histopathology In Skin Of Ratsmentioning
confidence: 71%